Mitofusin gain and loss of function drive pathogenesis in Drosophila models of CMT2A neuropathy. (3rd July 2020) - El Fissi, Najla; Rojo, Manuel; Aouane, Aїcha; Karatas, Esra; Poliacikova, Gabriela; David, Claudine; Royet, Julien; Rival, Thomas
Abstract :